Analisis Perilaku Pencegahan Keputihan pada Remaja Putri berdasarkan Teori Health Promotion Model (HPM) - Frida Rachmadianti; Ni Ketut Alit Armini; Aria Aulia Nastiti (Universitas Airlangga, 2019)
Introduction: The behavior of prevention of vaginal discharge in adolescents is still a health problem that needs attention. Vaginal discharge will have a harmful impact on adolescents, that is infection, pelvic inflammatory disease, infertility and malignancy (tumors and cancer). The HPM theory emphasizes the active role of someone in regulating the behavior of preventing an illness. The purpose of this study was to analyze the factors associated with the behavior of prevention of vaginal discharge in young women based on the Health Promotion Model (HPM) theory.Methods: The design of this study was analytical descriptive with a cross-sectional approach. Sampling uses simple random sampling technique. Large sample of 140 female students. Independent variables are self motivation, perceived benefits, interpersonal influences, and action commitment and the dependent variable is whiteness prevention behavior. The instrument used was a questionnaire. Analysis using logistic regression statistical test with α ≤ 0.05.Results: Factors related to whiteness prevention behavior were self motivation (p = 0,000), perceived benefits (p = 0,000), interpersonal influences (p = 0,020), and unrelated actions commitment (p = 0,102).Conclusion: The majority of female students have good behavior, self-motivation, perceived benefits, high interpersonal influences will improve vaginal prevention behavior. However, the commitment of actions does not contribute to the prevention behavior of vaginal discharge.